Anti-inflammatory effect of (-)-epigallocatechin-3-gallate on Porphyromonas gingivalis lipopolysaccharide-stimulated fibroblasts and stem cells derived from human periodontal ligament - Jung, Im-Hee; Lee, Dong-Eun; Yun, Jeong-Ho; Cho, Ah-Ran; Kim, Chang-Sung; You, Yoon-Jeong; Kim, Sung-Jo; Choi, Seong-Ho (Journal of periodontal & implant science, 2012)
(-)-epigallocatechin-3-gallate (EGCG) has been reported to exert anti-inflammatory and antibacterial effects in periodontitis. However, its exact mechanism of action has yet to be determined. The present in vitro study evaluated the anti-inflammatory effects of EGCG on human periodontal ligament fibroblasts (hPDLFs) and human periodontal ligament stem cells (hPDLSCs) affected by bacterial lipopolysaccharide (LPS) extracted from Porphyromonas gingivalis. hPDLFs and hPDLSCs were extracted from healthy young adults and were treated with EGCG and/or P. gingivalis LPS. After 1, 3, 5, and 7 days from treatment, cytotoxic and proliferative effects were evaluated using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and bromodeoxyuridine assay, respectively. And then, the gene expressions of hPDLFs and hPDLSCs were observed for interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL), and RANKL/OPG using real-time polymerase chain reaction (PCR) at 0, 6, 24, and 48 hours after treatment. The experiments were performed with the following groups for hPDLFs and hPDLSCs; 1) No treat, 2) EGCG alone, 3) P. gingivalis LPS alone, 4) EGCG+P. gingivalis LPS. The 20 µM of EGCG and 20 µg/mL of P. gingivalis LPS had the lowest cytotoxic effects, so those concentrations were used for further experiments. The proliferations of hPDLFs and hPDLSCs increased in all groups, though the 'EGCG alone' showed less increase. In real-time PCR, the hPDLFs and hPDLSCs of 'EGCG alone' showed similar gene expressions to those cells of 'no treat'. The gene expressions of 'P. gingivalis LPS alone' in both hPDLFs and hPDLSCs were highly increased at 6 hours for IL-1β, IL-6, TNF-α, RANKL, and RANKL/OPG, except the RANKL/OPG in hPDLSCs. However, those increased gene expressions were down-regulated in 'EGCG+P. gingivalis LPS' by the additional treatment of EGCG. Our results demonstrate that EGCG could exert an anti-inflammatory effect in hPDLFs and hPDLSCs against a major pathogen of periodontitis, P. gingivalis LPS.